1999
DOI: 10.1046/j.1365-2664.1999.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

The population dynamics of Anisantha sterilis in winter wheat: comparative demography and the role of management

Abstract: Summary 1. We report on a 3‐year field study designed to monitor the detailed population dynamics of Anisantha sterilis in winter wheat, as well as to explore the consequences of changing broad‐scale patterns of management, in the form of reduced fertilizer inputs. 2. In the absence of herbicides, population dynamics were dominated by density‐dependent population growth. Unusually, this occurred mainly through density‐dependent recruitment. This was estimated to reduce population growth rates by 50‐fold, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The results for E. plantagineum correspond well with these conclusions and provide further evidence of the often critical importance of the recruitment process in the determination of population size and in determining the success of a plant invasion. More recently, studies on annual weed species have suggested that some population demographic parameters may remain remarkably constant both spatially and temporally (Freckleton & Watkinson 1998; Lintell Smith et al . 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The results for E. plantagineum correspond well with these conclusions and provide further evidence of the often critical importance of the recruitment process in the determination of population size and in determining the success of a plant invasion. More recently, studies on annual weed species have suggested that some population demographic parameters may remain remarkably constant both spatially and temporally (Freckleton & Watkinson 1998; Lintell Smith et al . 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This form of recruitment thus sets a fixed upper limit to population size and has an extremely stabilizing effect on population dynamics. Notably, the maximal finite rate of increase of the population of Anisatha sterilis described by Lintell Smith et al . (1999) was greater than 100 individuals individual −1 year −1 and hence should have been capable of revealing any source of intrinsic instability.…”
Section: Lack Of Overcompensating Yield–density Responsesmentioning
confidence: 95%
“…Other stages of the life cycle have also provided evidence for density dependence within the course of a single growing season. In the arable weed Anisantha sterilis , for example, it was found that the proportion of seeds emerging from the seed bank declined as a function of density (Lintell Smith et al . 1999).…”
Section: Lack Of Overcompensating Yield–density Responsesmentioning
confidence: 99%
See 2 more Smart Citations